2022
DOI: 10.3389/fnut.2022.850004
|View full text |Cite
|
Sign up to set email alerts
|

Higher Coffee Consumption Is Associated With Reduced Cerebral Gray Matter Volume: A Mendelian Randomization Study

Abstract: BackgroundRecently published two-sample Mendelian randomization (MR) studies showed that genetically predicted coffee consumption may be associated with increased risk of Alzheimer’s disease and intracerebral hemorrhage but associated with a decreased risk of small vessel ischemic stroke. We aimed to investigate the effects of genetically predicted coffee consumption on magnetic resonance imaging (MRI) markers of cerebral small vessel disease and brain volume using the two-sample MR method.MethodsTwelve single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…In the present study, we observed an inverse association between current coffee consumption and striatal volume in controls and between coffee cups consumed per day and striatal volume in current consumers of PD and controls. Recently, using the data from UK Biobank, several large‐scale studies revealed an inverse association between coffee consumption and gray matter volume 17,18 . Moreover, the finding of this inverse association was supported by a double‐blind randomized controlled trial (RCT) 35 .…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…In the present study, we observed an inverse association between current coffee consumption and striatal volume in controls and between coffee cups consumed per day and striatal volume in current consumers of PD and controls. Recently, using the data from UK Biobank, several large‐scale studies revealed an inverse association between coffee consumption and gray matter volume 17,18 . Moreover, the finding of this inverse association was supported by a double‐blind randomized controlled trial (RCT) 35 .…”
Section: Discussionmentioning
confidence: 96%
“…Recently, using the data from UK Biobank, several large-scale studies revealed an inverse association between coffee consumption and gray matter volume. 17,18 Moreover, the finding of this inverse association was supported by a double-blind randomized controlled trial (RCT). 35 A total of 20 healthy male habitual caffeine consumers were recruited for the RCT study.…”
Section: Dorsal Striatum Consists Of Dorsomedial Striatum (Caudate)mentioning
confidence: 95%
See 2 more Smart Citations
“…Other studies have found that diet or eating behaviors could impact brain volumes ( 43 45 ). For example, a recent Mendelian randomization study found inverse association between coffee consumption and gray matter volume ( 46 ). It has been suggested that a larger brain volume provides a greater cerebral reserve against the effects of AD, maintaining cognitive function in the presence of neurodegeneration ( 47 ).…”
Section: Discussionmentioning
confidence: 99%